SOCIAL TYPES IN TRANSITIVE SOCIETY - Svetlana N. Yaremenko; Tamara A. Bondarenko; Ekaterina G. Kurova (Advanced Engineering Research)
Some sociocultural and social-psychological personality characteristics in the transitive society are analyzed. The effect of such determinants as apathy and vacuum on the human behaviour is shown. The characteristics of ‘mass man’, ‘resting man’, ‘paradoxical man’ are presented.